The shrews (Cryptotis) of Colombia: What do we know about them? - Noguera-Urbano, Elkin A.; Colmenares-Pinzón, Javier E.; Villota, Johana; Rodríguez-Bolaños, Abelardo; Ramírez-Chaves, Héctor E. (THERYA, 2019)
In Colombia, shrews (Cryptotis) are represented by seven species associated with Andean, high Andean, and Paramo ecosystems of the three national Cordilleras. Of these species, five are endemic to the Andean region of the country. Despite representing the group of mammals with the highest rate of endemic species, the knowledge currently available on aspects such as natural history, distribution, and ecology is limited. This work assesses the current state of knowledge of the shrews of Colombia, discusses taxonomic issues, risks and threats related to conservation, and identifies research needs and priorities. We compile the information on shrews of Colombia available in the literature and databases. We include two of the known species of the country and one to be determined within a phylogenetic context. In general, the knowledge of the shrews of Colombia reveals the lack of ecological and genetic studies. There are unsolved taxonomic questions about the presence of certain species in the different mountain ranges of the country. There is an urgent need to generate molecular information to clarify the richness of the genus in Colombia which, according to our observations, has been underestimated. The knowledge about the shrews of Colombia is still scarce, even when some species were first described more than a hundred years ago. The need to conduct systematic studies and comprehensive morphological descriptions to clarify the richness of the shrews of Colombia is highlighted.